Care Patterns and Overall Survival in Patients With Early-Onset Metastatic Colorectal Cancer. Issue 12 (December 2021) - Kanter, Katie; Fish, Madeleine; Mauri, Gianluca; Horick, Nora K.; Allen, Jill N.; Blaszkowsky, Lawrence S.; Clark, Jeffrey W.; Ryan, David P.; Nipp, Ryan D.; Giantonio, Bruce J.; Goyal, Lipika; Dubois, Jon; et al.
Abstract : PURPOSE: Colorectal cancer (CRC) incidence in patients younger than 50 years of age, commonly defined as early-onset (EO-CRC), is rising. EO-CRC often presents with distinct clinicopathologic features. However, data on prognosis are conflicting and outcomes with modern treatment approaches for metastatic disease are still limited. MATERIALS AND METHODS: We prospectively enrolled patients with metastatic CRC (mCRC) to a biobanking and clinical data collection protocol from 2014 to 2018. We grouped the cohort based on age at initial diagnosis: < 40 years, 40-49 years, and ≥ 50 years. We used regression models to examine associations among age at initial diagnosis, treatments, clinicopathologic features, and survival. RESULTS: We identified 466 patients with mCRC (45 [10%] age < 40 years, 109 [23%] age 40-49 years, and 312 [67%] age ≥ 50 years). Patients < 40 years of age were more likely to have received multiple metastatic resections (odds ratio [OR], 3.533; P = .0066) than their older counterparts. Patients with EO-CRC were more likely to receive triplet therapy than patients > 50 years of age (age < 40 years: OR, 6.738; P = .0002; age 40-49 years: OR, 2.949; P = .0166). Patients 40-49 years of age were more likely to have received anti-EGFR therapy (OR, 2.633; P = .0016). Despite differences in care patterns, age did not predict overall survival. CONCLUSION: Despite patients with EO-CRC receiving more intensive treatments, survival was similar to the older counterpart. However, EO-CRC had clinical and molecular features associated with worse prognoses. Improved biologic understanding is needed to optimize clinical management of EO-CRC. The cost-benefit ratio of exposing patients with EO-CRC to more intensive treatments has to be carefully evaluated.